A taxonomic synopsis of the genus Zornia J.F.Gmel. (Leguminosae: Papilionoideae) for the Neotropics - Zeferino, Laís Couto; Lewis, Gwilym Peter; Pezzini, Flávia Fonseca; Fortuna-Perez, Ana Paula (Acta Botânica Brasílica, 2025)
ABSTRACT The genus Zornia J.F.Gmel. (Leguminosae: Papilionoideae) includes around 80 species and is unique in the Adesmia clade for its pantropical distribution. Despite its ecological significance, taxonomic studies on Zornia are scarce. There is no information on the conservation status of its species, although many of which are narrowly endemics. This study updates the taxonomic and distributional knowledge of Zornia in the Neotropics and includes an identification key, field photographs, maps and conservation assessments based on IUCN Red List criteria. The research involved reviewing literature and analyzing specimens from 50 herbarium collections, documenting 50 species in the Neotropics. Conservation assessments indicate significant concerns for many Zornia species, with only three classified as Least Concern. Additionally, the study provides second-step lectotypifications for two species and re-establishes two other names at species rank. This study contributes to a refined understanding of Zornia taxonomy and emphasizes the need for targeted conservation efforts in the Neotropics.